STRATEGI GURU DALAM PENCAPAIAN KRITERIA KETUNTASAN MINIMAL (KKM) DI MASA PANDEMI COVID-19 PADA MATA PELAJARAN GEOGRAFI KELAS XI IPS DI MAN 1 KERINCI DAN SMAN 6 KERINCI - Santika, Akila Afra; Rahmanelli, Rahmanelli (JURNAL BUANA, 2023)
Learning strategy is one of the factors that can affect the success of a learning. The success of student learning can be measured by the achievement of student learning outcomes based on the standard minimum learning completeness criteria (KKM) that have been set. The purposes of this study: 1) To describe how the learning strategies used by Geography subject teachers in achieving KKM during the Covid-19 pandemic class XI IPS at MAN 1 Kerinci and SMAN 6 Kerinci, 2) To describe how the achievement of KKM in subjects Geography class XI IPS at MAN 1 Kerinci and SMAN 6 Kerinci, 3) To describe how the obstacles faced by Geography subject teachers in carrying out learning strategies for achieving KKM during the covid-19 pandemic in Geography class XI IPS at MAN 1 Kerinci and SMAN 6 Kerinci. This research was conducted in class XI IPS MAN 1 Kerinci and SMAN 6 Kerinci. The results of this study are useful for teachers, students and schools in achieving the KKM of students. This type of research is qualitative. Data collection techniques were carried out by observation, interviews, and documentation. Data analysis used in this research is data collection, data reduction, data presentation and conclusions. The results of the study show that: 1) Learning strategies: a) preliminary activities: the teacher makes lesson plans for one semester. Pre-learning activities are carried out with a pre-test in the form of questions and answers. b) delivery of information: the learning method used is the lecture method and the question and answer method. The media used are teacher's speech, pictures, textbooks, and videos. c) Student participation, student interaction with the teacher is one-way and two-way interaction patterns, while the interaction between students occurs when using the question and answer method and the game method. d) Test: the form of test used by the teacher to evaluate is in the form of an essay. e) follow-up activities: students whose scores have not reached the KKM perform remedial activities. 2) out of a total of 46 students, there are 87% of students or the equivalent of 40 students getting scores above the KKM standard and 13% of students or equivalent to 6 students whose scores have not reached the KKM standard. 3) the obstacles faced are limitations in choosing learning media due to inadequate school facilities and infrastructure, many students are also less active during the learning process, and the school yard is quite narrow and the school is also located in residential areas making noise from outside the classroom. can enter and interfere with the concentration of students during learning activities.